Fabrication of a Laser-Welded Fixed–Detachable Prosthesis for Immediate Loading - Shang-lun Kuo, DDS, MS;1 Tamer El-Gendy, DDS, MS;2 (Journal of Prosthodontics, 2006)
Immediate loading of dental implants in completely edentulous patients is receiving great attention.